2007
DOI: 10.1253/circj.71.1234
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Associates With Adiponectin Predominantly in Subjects With Metabolic Syndrome

Abstract: Background Inflammation and the metabolic syndrome (MetS) are important risk factors in cardiovascular disease. There is accumulating evidence that decreased adiponectin levels are associated with MetS. Recently, it was shown that adiponectin induces the expression of a potent anti-inflammatory cytokine, interleukin (IL)-10, in vitro. The aim of this study is to investigate the association of IL-10 levels with other pro-inflammatory and anti-inflammatory factors including adiponectin levels in vivo. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
0
28
0
3
Order By: Relevance
“…37 Contrary to the evidence showing antiinflammatory properties of smoking in monocytemacrophages, most 38,39 but not all studies 40 have reported a negative correlation between cigarette smoking and adiponectinemia, a well-known antiinflammatory adipokine that increases PPARG and insulin sensitivity. However, the negative correlation between adiponectinemia and IR (and/or MetS) [41][42][43] has not always been observed. [44][45][46] In addition, it remains unclear whether hypoadiponectinemia is a consequence or cause of obesity, IR and MetS.…”
Section: Circulation Journal Vol73 November 2009mentioning
confidence: 99%
“…37 Contrary to the evidence showing antiinflammatory properties of smoking in monocytemacrophages, most 38,39 but not all studies 40 have reported a negative correlation between cigarette smoking and adiponectinemia, a well-known antiinflammatory adipokine that increases PPARG and insulin sensitivity. However, the negative correlation between adiponectinemia and IR (and/or MetS) [41][42][43] has not always been observed. [44][45][46] In addition, it remains unclear whether hypoadiponectinemia is a consequence or cause of obesity, IR and MetS.…”
Section: Circulation Journal Vol73 November 2009mentioning
confidence: 99%
“…In the present study, we measured carotid artery inti-tudinal images (anterior oblique, lateral, and posterior oblique) of the left common carotid artery (CCA) of a 1.0-1.5 cm section at the distal end of the CCA proximal to the carotid bulb was obtained as described previously [15,16]. Mean IMT was obtained using computer software (IntimaScope, SoftMedical Co., Ltd, Tokyo, Japan) that automatically traces the intima-media edge of the far wall [17].…”
mentioning
confidence: 99%
“…However, the cause and effect relationship between the adiponection level and the ratio sd-LDL-C/LDL-C remains to be elucidated. 24 Interestingly, Jang et al reported that the presence of a G allele in the adiponectin gene at SNP 276 is correlated with greater oxidative stress, higher sd-LDL-C concentrations and smaller LDL particle size. 25 One of the mechanisms that link hypoadiponectinemia with the increase in the ratio sd-LDL-C/LDL-C might be insulin resistance caused by low adiponectin levels in MS patients.…”
Section: Discussionmentioning
confidence: 99%